Transformasi Bisnis di Era Digital: Peran Strategis Kecerdasan Buatan dalam Inovasi dan Keunggulan Bersaing - I Putu Putra Astawa; Ida Ayu Utari Dewi (RESI : Jurnal Riset Sistem Informasi, 2025)
Digital transformation has become a major driving force in the changing landscape of modern business. This study aims to examine the strategic role of artificial intelligence (AI) in supporting innovation and achieving competitive advantage in the digital era. Using a qualitative descriptive approach based on a literature review, this study analyzes various empirical and theoretical findings related to the implementation of AI in a business context. The results indicate that AI plays a crucial role in process automation, big data analysis, and improving the quality of consumer-oriented decision-making. In addition to driving operational efficiency, AI also opens up opportunities for product innovation and new, more adaptive, customer-driven business models. However, the implementation of AI is not without challenges such as digital infrastructure readiness, human resource competency gaps, and issues of data ethics and regulation. Therefore, integrating AI into business strategy requires a holistic, collaborative approach based on responsible governance. This research provides conceptual and practical contributions in designing AI-based digital transformation strategies, while also serving as a reference for policymakers and business actors to strengthen sustainable competitiveness.